PENGARUH KEBERADAAN SPESIES INVASIF TERHADAP KOMPOSISI DAN KELIMPAHAN JENIS VEGETASI DI DALAM SOIL SEED BANK DI PADANG PENGGEMBALAAN SADENGAN TAMAN NASIONAL ALAS PURWO - , Sri Mekar Dyah Wijayanti ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The species invasion of enceng-enceng (Cassia tora) and kerinyu (Chromolaena odorata) in Sadengan savanna since 1999 and gained its climax in 2003 until nowadays. The influence and the impact of species invasion are not only on the composition of surface biodiversity, but also on the composition and abundance of soil seed bank This research aims to find out the influence of invasive species on the composition and abundance of vegetation species in soil seed bank. The research is conducted in Sadengan savanna, Alas Purwo National Park by analyzing soil samples and running germination test to soil seed bank in the habitat which is invaded by enceng-enceng and kerinyu. The sampling method employs Stratified sampling method, by purposively placing sample plots in 1 x 1 meter quadrant in each stratification, with 15 sample plots. Collected data consists of soil surface vegetation species, physical properties (texture, bulk density, and porosity) and chemical properties (pH, C-Organik, N-total), the total and vegetation species of the germination test in soil seed bank. The physical and chemical properties of the soil are analyzed in the laboratory. Meanwhile, the germination test of soil seed bank calculates species diversity by using Shannon-wiener index. The species composition is analyzed using Sorensen index. The abundance is analyzed using Hillâs formula and the influence of soil depth on seed availability is analyzed using Pearson statistics test. The result shows that the percentage of silt from three sample plot location in 1 x 1 meter quadrant is higher than the percentage of sand and clay. They consist of 21.425 % sand, 56.57 % silt and 21.587 % clay, with silty loam texture soil. The bulk density is 1.1-1.2 gr/cm3, its porosity ranges 50%-53.191% and the average pH is 6.96. The content of organic carbon is 2.14-3.08 and N-total is 0.175-0.2. Based on the analysis of species diversity index (Hâ) shows that species diversity in the three habitats are low (Hâ < 2). The result of germination test in soil seed bank has 33 species, in which 24 pecies found in soil seed bank and surface vegetation, with seed density 2,857 individual seeds /m3. The highest seed density at 0-5 cm depth and it decreases along with the increase of soil depth, with correlation value (-0.988). In addition, the result shows a relatively high species composition similarity between soil seed bank and surface vegetation, with the value of 0.6234 and species abundance 3.12. The contribution of soil seed bank on invasive species regeneration is relatively small.